Study of the Sheyuegou dam breach – Experience with the post-failure investigation and back analysis. (July 2021) - Yu, Shu; Zhang, Qiang; Chen, Zuyu; Hao, Jianwei; Wang, Lin; Li, Peng; Zhong, Qiming
Highlights: A new calculation method for dam-break flood in low-data areas. Comprehensive review of available information on Sheyuegou dam breach. A rare case study on the failure process of an asphalt core dam. Propose the failure model parameters through laboratory testing and the flood mark. Back analysis the failure process through the established model (DB-IWHR). Abstract: Documenting dam burst cases is of prime importance to improve understanding of dam failure mechanisms and the ability to predict dam breach floods during emergencies. However, the relevant dam burst information has rarely been reported because of the sudden occurrence of the failure and the lack of nearby gauging stations for many small-scale dams. This paper advocates a comprehensive study of the available field information that could be obtained during and after dam failure, which may be incomplete and include uncertainties but still is useful. On July 31, 2018, the Sheyuegou Dam in Hami City, Xinjiang, China broke because of rainfall-induced flooding that had considerably exceeded the specified standard for small dams. The disaster resulted in 20 deaths and 8 people missing. This study presents the authors' field work after the dam failure that includes: (1) collection of the meteorological and hydrologic information, (2) interpretation of a witness's video that records the breach process, (3) aerial scan of the residual body of the dam, and (4) a survey of the flood high water marks. In combination with laboratory hydraulic and geotechnical property tests and the analysis using a physically-based dam breach model (DB-IWHR), this case history is analyzed with comparisons to the information obtained in the field. The review confirmed, in general, the usefulness of the existing dam failure analysis method and helped calibrate the various input parameters involved in these models. It is suggested that more dam breach cases be documented by on-site drone or mobile phone video and post-failure investigations from which a database or inventory on dam breaches can be established although some of them may be information-incomplete and fault-tolerant.